Achieving Persistent Room Temperature Phosphorescence and Remarkable Mechanochromism from Pure Organic Luminogens. (10th September 2015) - Gong, Yongyang; Chen, Gan; Peng, Qian; Yuan, Wang Zhang; Xie, Yujun; Li, Shuhong; Zhang, Yongming; Tang, Ben Zhong
<x xml:space="preserve">Abstract</x> Persistent room temperature phosphorescence (RTP) from pure organic luminogens can be rationally realized based on the crystallization‐induced phosphorescence phenomenon and severe crystallization. A perfect crystal with dense molecular packing and effective intermolecular interactions isolates the triplet excitons from quenching sites and significantly blocks the high‐energy vibrational dissipation, thus yielding long‐lasting RTP.